Maqashidiyah Dimensions on the Story of Sodom in the Qur'an Letter Al-Araf Verses 80-81 - Mujaddi, Lalu Riastata Al; Ashri, Zainul (Journal of Islamic Thought and Philosophy, 2024)
Stories in the Qur'an have various interpretations and dominantly tend to tell stories like storytelling in general. This happens because of the method and intellectual background of the mufasir. Despite this, story verses in the Qur'an have a fairly important position and even the Qur'an is dominated by story verses. This indicates that a more in-depth study of the verses of stories in the Qur'an is needed so that the purpose, maqashid or maghza of the verse can be understood and the lessons (‘ibrah) from the previous story are applied to the present day. Therefore, this paper will try to reveal the deepest message of the homosexual story in Qs. al-A'raf [7]: 80-81 with the method of tafsir maqashidi by Abdul Mustaqim. With a library research, descriptive-analysis and tafsir maqashidi method, this paper produces findings: after conducting a fairly in-depth analysis of the story of sodomy in Qs. Al-A'raf [7]: 80-81, the main message contained in the verse is for hifzh an-Nafs or self-preservation as a foothold for improving social order as well as hifzh ad-Daulah, so that the surrounding community does not fall into homosexuality like the previous Sodomites which caused the descent of Allah's punishment which can damage the natural environment or bring natural disasters.